Development of living museum and storynomic tourism based on tri hita karana in kaba-kaba village, tabanan bali - Made Mutiara Putri Udayani; Putu Eka Wirawan; I Gede Krisna Yoga Putra Pratama (Institut Pariwisata dan Bisnis Internasional, 2021)
Tourism is currently the sector most affected by the COVID-19 outbreak. However, the momentum of this pandemic is considered a transition period to reorganize Indonesia's tourism. One of them is the development of the tourism sector in the development of tourist villages. The tourism interest that occurred made the author of this study conceptualizes the development of special interest tourism with the concept of living museum and storynomic tourism located in Kaba-Kaba Village, Tabanan, Bali based on Tri Hita Karana. The concept was chosen because Kaba-Kaba Village has a cultural heritage in the form of Puri in which there is an ancient site. This research uses qualitative methods with a data approach through observation in the form of interviews and literature studies. The results showed that the concept of living museum and storynomic tourism is very appropriate for the development of Kaba-Kaba tourist village because tourist products in the form of relics of historical heritage sites become a capital of interest for the development of special interest tourism. With the development of Living Meseum and Storynomic Tourism where Tri Hita Karana as the foundation of cultural tourism can directly fall into the hands of the community where this makes the tourist village that is directly managed by local champions in Kaba-Kaba Village.